The role of specialist palliative care services in cancer survivorship - Taylor, Amy Grace (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2026)
Given the advancements in cancer treatments and outcomes, more people are living longer with, through and beyond cancer. All these individuals may be referred to as cancer survivors. Many also live with adverse consequences of cancer and its treatment, even though they may have no evidence of disease. Specialist palliative care services (SPCS) provide holistic care (physical, psychological, social and spiritual) for individuals with health-related suffering and those close to them. Historically, SPCS have cared for people with advanced cancer and towards the end of life. Most people on anticancer treatment or with no evidence of disease do not have access to SPCS, despite having an array of unmet needs. There is much contention about the role of SPCS for these groups, and surrounding the terminology used to describe them. This thesis aims to establish the potential role of SPCS for the different cohorts of people who have or had cancer, to determine the views of people with cancer about the terms used to describe them, and to use these findings to develop a new model of care. A narrative literature review on the role of SPCS for people living beyond cancer demonstrated many synergies between the core activities of SPCS, the essential components of survivorship care, and the unmet needs of this group, but limited data on the actual involvement of SPCS, and potential barriers. A scoping review on the meaning and acceptance of the term cancer survivor identified diverse results, and showed that the views of all groups of people who have or had cancer have not been identified. In a European electronic Delphi study, 86 specialist palliative care experts, and 54 oncology experts (including professionals and patient advocates), reached consensus that cancer survivor terminology should be applied to people post-treatment with no evidence of disease, and about the roles of SPCS in supporting people with stable disease, and people living beyond cancer. A multi-site cross-sectional survey-based study assessing the perspectives of a heterogeneous group of 1328 people with cancer in Ireland and the United Kingdom (UK) on the terms used to describe them revealed mixed perceptions regarding cancer survivor, but a trend towards disliking being described by the term, although most found it acceptable for people with no evidence of disease. Results suggest that application of cancer survivors to people with active cancer should be reconsidered. Considering all outcomes, a model of SPCS for people who have or had cancer has been proposed, requiring further research to identify if it can improve the care of people who have or had cancer.
APPROVED
Keywords: palliative care; cancer survivors; cancer survivorship; living with cancer; living beyond cancer